STRATEGI YANG DIGUNAKAN INDO MARKETING SOLUTION UNTUK MENCIPTAKAN BRAND AWARENESS MAJALAH LAHAP - Ellora Oktavia (Universitas Ciputra Surabaya, 2016)
Brand Awareness is one way of branding strategy that can create emotional connection. The aim of this qualitative research is to determine the appropriate strategies for Indo Marketing Solution to improve the brand awareness of Lahap magazine. The informants of this study include Magdalena, Wendo, and Aland as the owners of Overview Magazine, Magazine Publicity, and Magazine 555 respectively. The indicators used in this study are brand, brand awareness with top-of-mind awareness (TOMA) approach, brand image, and brand awareness strategy. Hermeneutical analysis is used as analysis tool in this study. This method allows informants to tell stories about the time they first start their business. The result of this research confirms the importance of brand for the three informants. They believe that people recognize the services offered and the brand itself from the company's brand. Additionally, building brand image is essential in creating brand awareness. If a company has a good brand image, the public's perception of the brand will be favorable. In fact, good brand image may also result in customer loyalty. There are many ways to build brand image, such as issue release schedule consistency and concept depth. Meanwhile, some of the strategies to create brand awareness include creating good reputation, convincing the public to accept the objectives of the company, utilizing active media, maintaining logo appeal consistency, and collaborating with advertising partners which have wide networks. Other important strategies for a media corporation involve being objective and ensuring that the reality is in line with the journalism code of ethics.